Acute myeloid leukemia management and research in 2025 - Hagop M. Kantarjian; Courtney D. DiNardo; Tapan M. Kadia; Naval G. Daver; Jessica K. Altman; Eytan M. Stein; Elias Jabbour; Charles A. Schiffer; Amy Lang; Farhad Ravandi (CA: A Cancer Journal for Clinicians, 2025)
Abstract The first 5 decades of research in acute myeloid leukemia (AML) were dominated by the cytarabine plus anthracyclines backbone, with advances in strategies including allogeneic hematopoietic stem cell transplantation, high‐dose cytarabine, supportive care measures, and targeted therapies for the subset of patients with acute promyelocytic leukemia. Since 2017, a turning point in AML research, 12 agents have received regulatory approval for AML in the United States: venetoclax (BCL2 inhibitor); gemtuzumab ozogamicin (CD33 antibody–drug conjugate); midostaurin, gilteritinib, and quizartinib (fms‐like tyrosine kinase 3 inhibitors); ivosidenib, olutasidenib, and enasidenib (isocitrate dehydrogenase 1 and 2 inhibitors); oral azacitidine (a partially absorbable formulation); CPX351 (liposomal encapsulation of cytarabine:daunorubicin at a molar ratio of 5:1); glasdegib (hedgehog inhibitor); and recently revumenib (menin inhibitor; approved November 2024). Oral decitabine‐cedazuridine, which is approved as a bioequivalent alternative to parenteral hypomethylating agents in myelodysplastic syndrome, can be used for the same purpose in AML. Menin inhibitors, CD123 antibody–drug conjugates, and other antibodies targeting CD123, CD33, and other surface markers are showing promising results. Herein, the authors review the frontline and later line therapies in AML and discuss important research directions.